Mencegah Kecelakaan Kerja di Kapal dengan Penggunaan Inert Gas System - Mahendro, Iwan; Ihsan Setyadi, Hadyan (Majalah Ilmiah Gema Maritim, 2024)
The sea is where many ships travel to various destinations. One of the ships sailing on the sea is a tanker. The tanker was loaded with liquid material that was likely to be loaded with oil. Tankers loaded with oil have the possibility of accidents such as fire. It has been the case of ships that have experienced fires. One of the problems is that the use of an inert gas system has not been implemented on ships, even though this system is very helpful in minimizing the occurrence of fires on ships. With this research, it can be expected that we know the method of operating the inert gas system and the working system of the inert gas on the tanker. In this study, I used several methods, namely: Conservation, Interviews, Documents, and literature in this way the author got some data to get this research. The result of this study is to minimize the occurrence of accidents on ships.